2019
DOI: 10.1111/micc.12591
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the hemodynamic contribution of capillaries, arterioles, and collateral arteries to vascular adaptations in arterial insufficiency

Abstract: Objective There is currently a lack of clarity regarding which vascular segments contribute most significantly to flow compensation following a major arterial occlusion. This study uses hemodynamic principles and computational modeling to demonstrate the relative contributions of capillaries, arterioles, and collateral arteries at rest or exercise following an abrupt, total, and sustained femoral arterial occlusion. Methods The vascular network of the simulated rat hindlimb is based on robust measurements of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 59 publications
(174 reference statements)
0
11
0
Order By: Relevance
“…While several experimental studies have observed adaptations in collateral arteries and/or the distal microvasculature (arterioles and capillaries) following a major arterial occlusion on an acute time frame (see summary in), a comprehensive understanding of the relative significance of these adaptations is missing. In particular, previous studies that investigated the redistribution of vascular resistances post‐occlusion and that demonstrated the importance of collateral arteries were based solely on hemodynamic calculations and did not reveal the underlying factors that induced these changes in the vasculature. The results of this study provide a mechanistic explanation for the contributions of various vascular responses following an occlusion and identify the importance of the shear response in collateral arteries and the metabolic response in the distal microcirculation when compensating for an occlusion (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While several experimental studies have observed adaptations in collateral arteries and/or the distal microvasculature (arterioles and capillaries) following a major arterial occlusion on an acute time frame (see summary in), a comprehensive understanding of the relative significance of these adaptations is missing. In particular, previous studies that investigated the redistribution of vascular resistances post‐occlusion and that demonstrated the importance of collateral arteries were based solely on hemodynamic calculations and did not reveal the underlying factors that induced these changes in the vasculature. The results of this study provide a mechanistic explanation for the contributions of various vascular responses following an occlusion and identify the importance of the shear response in collateral arteries and the metabolic response in the distal microcirculation when compensating for an occlusion (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also offers an explanation for the reduced ability to compensate underexercising conditions that has been noted by other investigations . The model predicts that in the occluded case, the collaterals and arterioles are fully dilated before oxygen demand even reaches a level that corresponds to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous theoretical studies identified the primary role of collateral vessels in flow compensation following major arterial occlusion 9 and simulated vascular responses to occlusion on an acute time frame. 10 The study by Zhao et al 10 included a mechanistic description of flow regulation but did not allow for structural adaptation, and thus blood flow compensation was limited.…”
mentioning
confidence: 99%